Changes of Meaning in Rejang Language - Neza Epriani; Kasmantoni Kasmantoni; Heny Friantary (Yayasan Karinosseff Muda Indonesia, 2022)
This study aims to describe changes in meaning and the factors that cause changes in the meaning of the Rejang language in Ujung Tanjung Dua Village, Lebong Regency. The research method used in this study is a qualitative research method. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the change in meaning extends to the Rejang language which consists of six vocabularies, namely (1) awas, (2) Carai, (3) Esep, (4) Gen, (5) Gonong, (6) Mlai, the form of change in the meaning of amelioration consists of fifteen vocabularies, namely (1) Stir, (2) Inok, (3) Bisay, (4) Beleseng, (5) Bolon, (6) Ubo, (7) Danua, (8) Ganau, (9) Gupuak, (10) Jalet, (11) Nasea, (12) Ko os, (13) Mojoa, (14) Nokoa, (Pajuak). Based on the research, it can be concluded that there is a change in the meaning of the Rejang language in Ujung Tanjung Dua Village, Lebong Regency.